2017
DOI: 10.2174/1874325001711011023
|View full text |Cite
|
Sign up to set email alerts
|

Rationale of Cruciate Retaining Design in Rheumatoid Arthritis: A Review of Clinical Analysis and its Role in Rheumatoid Arthritis

Abstract: Background:Over the years, proponents of total knee designs (cruciate retaining and posterior stabilised) have conducted several long-term studies to claim the potential of these designs in several subsets of patients. Total knee arthroplasty (TKA) in patients with rheumatoid arthritis has also been one such domain where numerous studies were conducted in the past. A general perception among majority of arthroplasty surgeons is that, posterior stabilised (PS) is the implanted design of choice among patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…4 ). As a result of this box cut, the intercondylar notch would have been further weakened and the cyst defect would have been connected, creating a massive bone defect and increasing the risk of periprosthetic fractures [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 ). As a result of this box cut, the intercondylar notch would have been further weakened and the cyst defect would have been connected, creating a massive bone defect and increasing the risk of periprosthetic fractures [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have even suggested improved long-term survivorship with CR designs [ 14 ]. Advocates of CR designs in TKA cite long-term survivorship in addition to preservation of bone stock and controlled femoral rollback as advantages of this design over PS designs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammatory arthritis, such as rheumatoid arthritis, was previously reported to be one of the contraindications for CR TKA, 15 advances in implant design, surgical techniques, and rehabilitation have led to an expansion of the indications for CR TKA. Archibeck et al 16 and Dennis et al 17 suggested that CR TKA would yield satisfactory results in patients with rheumatoid arthritis.…”
Section: Preoperative Factors Predicting the Sacrificing Of Pclmentioning
confidence: 99%